Evidence for Marine Consumption During the Upper Palaeolithic at "El Pirulejo" Inland Rock-Shelter (Southern Iberia Peninsula, Spain). (5th May 2022) - Naito, Yuichi I.; Belmaker, Miriam; Jiménez-Espejo, Francisco J.; Simón-Vallejo, María D.; Riquelme Cantal, José Antonio; Parrilla-Giráldez, Rubén; Cortés-Sánchez, Miguel
During the Last Glacial Maximum and deglaciation, the Iberian Peninsula served as a faunal and human population refugium. Human foodways have always played a pivotal role in understanding social and cultural practices in prehistory. Nonetheless, the limited number of archaeological sites and human remains in this region hinders the complete understanding of these critical communities' diet. To increase our knowledge about human consumption patterns, we selected three Magdalenian levels from the site of El Pirulejo (Southern Iberia Peninsula, Spain). These levels are characterized by a high abundance of rabbit ( Oryctolagus cuniculus ) remains (76–97% MNI), initially suggesting that rabbits were the primary source of protein for site inhabitants. Stable isotope analysis was conducted on two human teeth in tandem with stable isotope analysis of the rabbit teeth. Contrary to the expectations derived from the zooarchaeological analysis, rabbits were not a significant source of dietary protein. Carbon and nitrogen bulk isotopic values are the most enriched found in sampled human remains for this area and context. Our data supports aquatic food resource inclusion and increased resource diversity among Iberian hunter-gatherers during the Magdalenian. This study is consistent with previous studies that suggested a socio-economic network among human groups between inland and coastal regions in the terminal Pleistocene Southern Iberia.